Pengaruh Penerapan Pengendalian Internal, Profesionalisme, Audit Investigasi, dan Akuntansi Forensik terhadap Pengungkapan Fraud - Nova Ramadani; Lintang Kurniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of internal control implementation, professionalism, investigative audit, and forensic accounting on fraud disclosure. The research employed a quantitative approach based on Agency Theory and used primary data collected through questionnaires distributed to inspectorate auditors in Wonogiri Regency, Surakarta City, and Karanganyar Regency. The sample was determined using purposive sampling with the Slovin formula. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS software through outer model testing, inner model testing, and bootstrapping. The findings reveal that professionalism and forensic accounting significantly influence fraud disclosure, while internal control implementation and investigative audit do not significantly affect fraud disclosure. These results indicate that auditor professionalism and the application of forensic accounting play an important role in improving the effectiveness of fraud disclosure within government institutions.